Improving Students' Vocabulary Mastery Using Linguistic Approach - I Ketut Warta (Universitas Negeri Malang, 2016)
It is taken for granted that students' vocabulary can be developed to a certain degree and its development can be done through a number of ways. This study investigated the effectiveness of linguistic approach in developing EFL learners' vocabulary. 50 participants were involved in the study. They were divided into experimental and controlled groups, consisting of 25 students. The experimental group was taught using linguistic method while the controlled was instructed with a conventional method. The experiment was carried out in the classroom setting and lasted for one semester. The two groups were evaluated by means of pre-and post-test. The results show that the experimental group performed better than the controlled. The value of t-test is bigger than the value of t-table, and assessment of student' performance level, by the help of two native speakers, shows significant development; it developed from marginal to modest or between modest and competent, or from basic level to intermediate with the mean difference of 1.76.